The Role Of Family Support In Childbirth: Implications For Maternal And Infant Well-Being - Sundary, Santi (Oshada, 2024)
Labor is a critical moment in the life of both mother and baby, often accompanied by physical and emotional challenges. Family support, whether emotional, physical, or informational, plays an important role in influencing the quality of the birth experience and health outcomes. This study used a qualitative approach with literature review as the main data collection technique. This study aims to explore the role of family support in the labor process and its implications for maternal and infant well-being. The literature study approach was used to identify and analyze various research, theories, and empirical reports relevant to the topic. The study results show that emotional support from family can reduce maternal anxiety, increase a sense of security, and improve the overall labor experience. Physical support, such as massaging or helping the mother move, contributes to a smoother labor process and minimizes the need for medical intervention. Informational support helps mothers understand the stages of labor and make better decisions regarding health care. In addition, family support improves the quality of care provided to the baby, helps the mother to be more responsive to the baby's needs, and supports a strong emotional bond between mother and baby. The implications of these findings emphasize the importance of family involvement in childbirth and the postpartum period to improve the well-being of mothers and infants. Health workers are advised to encourage family participation and provide adequate education on the role of family support, to ensure that mothers and infants receive optimal support.